2020
DOI: 10.36555/almana.v4i2.1410
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Promotion and Price on Purchase Decisions

Abstract: The progress of a business is closely related to business management, while the rate of growth of a company is influenced by many things such as product development, sales concepts, and marketing concepts, therefore the sales concept and marketing concept are inseparable from promotional activities. Promotional activities are activities to promote goods directly to attract prospective buyers to the products being promoted Along with the advancing development of the era of the need for fashion has become a sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 0 publications
2
6
0
1
Order By: Relevance
“…Another study on Nigerian consumers' behaviour found that consumers' awareness of socially responsible practices largely influenced their purchasing decisions (Potluri et al, 2020). On sales promotion, the current result is consistent with research conducted by Yusuf and Sunarsi (2020), who found that promotion and price concurrently have a significant effect on purchase decision.…”
Section: Results Of Hypotheses Testingsupporting
confidence: 90%
“…Another study on Nigerian consumers' behaviour found that consumers' awareness of socially responsible practices largely influenced their purchasing decisions (Potluri et al, 2020). On sales promotion, the current result is consistent with research conducted by Yusuf and Sunarsi (2020), who found that promotion and price concurrently have a significant effect on purchase decision.…”
Section: Results Of Hypotheses Testingsupporting
confidence: 90%
“…We suggest promotional benefits for products that are not complementary. On another occasion, Yusuf & Sunarsi (2020) concluded that the greater the promotion and price, the greater the buying interest will be. In addition, the emotional bond between sellers and customer needs to be strengthened by distribution, promotion, and prices that apply to their income levels (Al Badi, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Hasil penelitian menunjukkan persepsi harga bukan sebagai faktor yang memengaruhi keputusan belanja. Hasil ini berbeda dengan penelitian Yusuf & Sunarsi (2020) menemukan bahwa persepsi harga menjadi faktor penentu keputusan pembelian, sertya penelitian Anggita & Ali (2017), Pramudana & Santika (2018), Megawati & Marlina (2020) yang menunjukkan bahwa persepsi harga berpengaruh signifikan terhadap keputusan pembelian. Hasil penelitian ini bisa disebabkan oleh beban volume pengiriman dari ekspedisi yang akan menambah harga yang dibebankan ke konsumen.…”
Section: Pembahasanunclassified